Városmarketing az Interneten – lehetőségek és eredmények - Fojtik, János (Tér és Társadalom, 1999)
City marketing seems not to be a typical, frequently cultivated area of marketing. The terms „local marketing", „regional marketing" appeared some 15 years ago in American and Western European publications. For today, this discipline is widely used and has arrived to Eastern Europe as well. City marketing is definitely in vogue in Hungary today. On-line marketing or Internet marketing (however, these terms are not the same in full meaning) is also a novum, a brand new field of marketing. To use on-line marketing tools means the same and offers the same to all of these countries. City marketing on-line probable does not have the traditional disadvantage s. The article is focusing on a visual investigation and categorisation of Internet sites and home pages of selected Hungarian cities, on how they use their presence on Internet, for what market segments and with what type of values. Web-site surveying is common to some business areas, especially the Fortune 100-500-1000 companies are investigated in many ways. As cities are slowly emerging in this marketing space, we think they should find their marketing tools and personalised style as well. A city does not market anything, but information and problem solving: this can be a service to citizens and for businessmen as well. The author is absolutely convinced that surveys like that can help for city management and web designers to utilise technology – for the benefit of all of us, citizens of an information society.